Silver Nanoparticles Induce Neutrophil Extracellular Traps Via Activation of PAD and Neutrophil Elastase - Kang, HanGoo (Biomolecules, 2021)
Silver nanoparticles (AgNPs) are widely used in various fields because of their antimicrobial properties. However, many studies have reported that AgNPs can be harmful to both microorganisms and humans. Reactive oxygen species (ROS) are a key factor of cytotoxicity of AgNPs in mammalian cells and an important factor in the immune reaction of neutrophils. The immune reactions of neutrophils include the expulsion of webs of DNA surrounded by histones and granular proteins. These webs of DNA are termed neutrophil extracellular traps (NETs). NETs allow neutrophils to catch and destroy pathogens in extracellular spaces. In this study, we investigated how AgNPs stimulate neutrophils, specifically focusing on NETs. Freshly isolated human neutrophils were treated with 5 or 100 nm AgNPs. The 5 nm AgNPs induced NET formation, but the 100 nm AgNPs did not. Subsequently, we investigated the mechanism of AgNP-induced NETs using known inhibitors related to NET formation. AgNP-induced NETs were dependent on ROS, peptidyl arginine deiminase, and neutrophil elastase. The result in this study indicates that treatment of 5 nm AgNPs induce NET formation through histone citrullination by peptidyl arginine deiminase and histone cleavage by neutrophil elastase.